Accountability in aid management - Hernadez, Diana Marie (Philippine Journal of Public Administration, 2010)
The importance of good governance, specifically in the presence of accountability among developing countries in managing development aid from official aid agencies, has been significantly recognized. The Republic of the Philippines has been struggling to address the issue of corruption not only in aid management but also in the government as a whole. The contribution of the accountability systems of a recipient government to address corruption in aid management and to make aid more effective is analyzed here.